Effects of Bedding Material on Equine Lower Airway Inflammation: A Crossover Study Comparing Peat and Wood Shavings - Mönki, Jenni; Saastamoinen, Markku; Karikoski, Ninja; Rajamäki, Minna; Raekallio, Marja; Junnila, Jouni; Särkijärvi, Susanna; Norring, Marianna; Valros, Anna; Oranen Ben Fatma, Silja; Mykkänen, Anna (Frontiers in Veterinary Science, 2021)
Bedding materials affect stable air hygiene, and thus the development and exacerbation of equine asthma. There is limited knowledge concerning the effects of various bedding materials on equine lower airway inflammation. The objective of our study was to investigate the effects of bedding materials on clinical respiratory signs, the tracheal mucus score, and lower airway cytology in healthy adult horses. The study design was a prospective controlled study, and the subjects were healthy adult riding school horses (n = 32) from a single stable. Wood shavings were compared to peat, which was used as a reference bedding material. Lower airway endoscopy and sampling (tracheal wash and bronchoalveolar lavage fluid) for cytological examination were performed after each 35-day bedding period. No difference between bedding periods was observed in the respiratory rate or tracheal mucus score. Tracheal wash neutrophil percentage with the wood shavings was higher compared to the previous (P = 0.040) or following (P = 0.0045) peat period. Bronchoalveolar lavage fluid neutrophil percentage with the wood shavings was higher compared to the following peat period (P <0.001). We conclude that compared to wood shavings, peat bedding is favorable when considering neutrophilic lower airway inflammation in horses. The information gained from this study may assist veterinarians and horse owners in selecting bedding materials, especially for horses suffering from equine asthma.